Application of Cryptography in Document Encryption Using Android-Based Rijndael Method - Dedek Kurniawan; Roy Fanry Siahaan; Hasanul Fahmi (Putaka Timur Publisher, 2021)
Document interception is the most feared thing by communication network users at this time. Currently, documents are very easy to be stolen, because the level of security of the document itself is often forgotten so that advanced security is needed in securing the document. One of the documents that will be secured is a PDF (Portable Document Format) file because the advantage is that it can be opened on any computer or even a smartphone without any changes to the data or contents. However, since the conversion from PDF to Word, many files have been manipulated so that PDF is very important to be safe. The increase in data theft, data piracy, and misuse of the data resulted in losses for the owner of the data, information, and documents. Cryptography is a good solution in securing data, cryptography has two techniques, namely encryption, and decryption where encryption is to change the data to be not understood while decryption returns the original data. There are many cryptographic algorithms such as Rijndael, Serpent, Twofish, MARS, RC6, MRC6, RSA, and others, Rijndael algorithm supports key lengths of 128 bits, 192 bits, and 256 bits. Lock length and block size can be selected independently. The encryption and decryption tests were carried out using the Android platform with the implementation carried out on an image measuring 300 x 300 pixels. Rijndael algorithm has image encryption speed is 174% faster. So, it can be concluded that the Rijndael Algorithm has advantages in doing encryption and decryption very quickly and better.